Accessing the Triplet State in Heavy‐Atom‐Free Perylene Diimides. Issue 14 (18th February 2016) - Yu, Zhenyi; Wu, Yishi; Peng, Qian; Sun, Chunlin; Chen, Jianwei; Yao, Jiannian; Fu, Hongbing
Abstract: Previous studies of perylenediimides (PDIs) mostly utilized the lowest singlet excited state S1 . Generation of a triplet excited state (T1 ) in PDIs is important for applications ranging from photodynamic therapy to photovoltaics; however, it remains a formidable task. Herein, we developed a heavy‐atom‐free strategy to prompt the T1 ←S1 intersystem crossing (ISC) by introducing electron‐donating aryl (Ar) groups at the head positions of an electron‐deficient perylenediimide (PDI) core. We found that the ISC efficiency increases from 8 to 54 % and then to 86 % by increasing the electron‐donating ability of head‐substituted aryl groups from phenyl ( p ‐PDI) to methoxyphenyl (MeO‐PDI) and then to methylthioxyphenyl (MeS‐PDI). By enhancing the intramolecular charge‐transfer (ICT) interaction from p ‐PDI to MeO‐PDI, and then to MeS‐PDI, singlet oxygen generation via energy‐transfer reactions from T1 of PDIs to 3 O2 was demonstrated with the highest yield of up to 80 %. These results provide guidelines for developing new triplet‐generating PDIs and related rylene diimides for optoelectronic applications. Abstract : Charge‐transfer interactions are introduced to the perylenediimide framework and lead to rapid intersystem crossing to yield 3 PDI*, providing a stuctural alternative for optoelectronic applications (see figure).